IMPACT OF PRODUCT DUMPING ON THE AGRICULTURAL SECTOR IN IRAQ (2009-2017) - & Jbara, Ghadhban (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this work was to check the presence of the dumping from neighboring countries of Iraq, Turkey and Jordan. The margin of dumping was calculated by taking the difference between the normal value and the export price. If it exceeds 2%, then there is dumping. Product dumping in Iraq has increased since 2003, and it is increasing from year to year for many types of agricultural and food commodities. Main reasons are the high rate of imports and the absence of trade policies represented by customs tariffs which in turn control the trade exchange. The research concluded that there is an intentional dumping in the trade of some agricultural commodities with Iraq from neighboring countries. Trade exchange with these countries has negative effects on the domestic product.